Information and Communication Technology for Intelligent Systems (ICTIS 2017) - Volume 1 - Satapathy, Suresh Chandra; Joshi, Amit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume includes 74 papers presented at ICTIS 2017: Second International Conference on Information and Communication Technology for Intelligent Systems. The conference was held on 25th and 26th March 2017, in Ahmedabad, India and organized jointly by the Associated Chambers of Commerce and Industry of India (ASSOCHAM) Gujarat Chapter, the G R Foundation, the Association of Computer Machinery, Ahmedabad Chapter and supported by the Computer Society of India Division IV - Communication and Division V - Education and Research. The papers featured mainly focus on information and communications technology (ICT) for computation, algorithms and data analytics. The fundamentals of various data analytics and algorithms discussed are useful to researchers in the field.
Survey on Online Social Media Networks Facebook Forensics -- Cooperative Biometric Multimodal Approach for Identification -- Hidden Decision Tree based Pattern Evaluation using Regression Models for Health Diagnosis -- A Security Approach and Prevention Technique against ARP Poisoning -- A High-Speed Image Fusion Method using Hardware and Software Co-Simulation -- Personalized Indian Bschool Counsellor System: A Rational Approach -- Proposed Model for an Expert System for Diagnosing Degenerative Diseases - Using Digital Image Processing with Neural Network.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence